Dragon road - Yep, Laurence, 1948- (Yep, Laurence, 1948- Golden mountain chronicles, 2008)
Cal and Barney, Chinese Americans, are trapped in a world of racial prejudice in 1939 with no jobs and no future until the Dragons, a barnstorming basketball team, invites them to join the team.